Transmission electron microscopy for the evaluation and optimization of crystal growth. Issue 5 (1st May 2016) - Stevenson, Hilary P.; Lin, Guowu; Barnes, Christopher O.; Sutkeviciute, Ieva; Krzysiak, Troy; Weiss, Simon C.; Reynolds, Shelley; Wu, Ying; Nagarajan, Veeranagu; Makhov, Alexander M.; Lawrence, Robert; Lamm, Emily; et al.
Abstract : In this article, the potential of transmission electron microscopy to assist in the process of generating well diffracting crystals for conventional crystallography, as well as for free‐electron laser and micro‐electron diffraction applications, is demonstrated. Abstract : The crystallization of protein samples remains the most significant challenge in structure determination by X‐ray crystallography. Here, the effectiveness of transmission electron microscopy (TEM) analysis to aid in the crystallization of biological macromolecules is demonstrated. It was found that the presence of well ordered lattices with higher order Bragg spots, revealed by Fourier analysis of TEM images, is a good predictor of diffraction‐quality crystals. Moreover, the use of TEM allowed (i) comparison of lattice quality among crystals from different conditions in crystallization screens; (ii) the detection of crystal pathologies that could contribute to poor X‐ray diffraction, including crystal lattice defects, anisotropic diffraction and crystal contamination by heavy protein aggregates and nanocrystal nuclei; (iii) the qualitative estimation of crystal solvent content to explore the effect of lattice dehydration on diffraction and (iv) the selection of high‐quality crystal fragments for microseeding experiments to generate reproducibly larger sized crystals. Applications to X‐ray free‐electron laser (XFEL) and micro‐electron diffraction (microED) experiments are also discussed.